The Implementasi Pembelajaran Akidah Akhlak di MI Darul Ulum Kota Bekasi - Andriyansyah, Andriyansyah (El Banar : Jurnal Pendidikan dan Pengajaran, 2021)
This research discusses how students become more moral and have character traits in their daily lives with good morals. Morals are evidence of human glory. Human glory will be seen if he is attached to noble morals. On the other hand, humans will become the creatures of the lowest value, when humans lose their humanity which is attached by Allah to humans. One of the morals that is applied is the morals of the Prophet Muhammad SAW, grounding the morals of the Prophet Muhammad in everyday life is a concrete step for shaping the character of students in Islamic educational institutions. Because the morals of the Prophet Muhammad are very relevant when applied today where moral decadence occurs everywhere. Keywords: Learning, Morals, Islamic Education.